2015
DOI: 10.4315/0362-028x.jfp-15-002
|View full text |Cite
|
Sign up to set email alerts
|

Development of Models To Relate Microbiological and Headspace Volatile Parameters in Stored Atlantic Salmon to Acceptance and Willingness To Prepare the Product by Senior Consumers

Abstract: Microbial spoilage of salmon occurs during extended refrigerated storage and is often accompanied by unpleasant aromas. When spoilage is detected, it is assumed that consumers will reject the product for consumption. Because sensory panels of trained individuals or consumers are expensive and labor intensive, identification of microbiological or chemical indicators to characterize the extent to which fish has spoiled is needed when experimental process and storage treatments are being evaluated. A consumer pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Volatile compounds have been shown to change during storage, which can be used as good indicators of fish spoilage or shelf-life instead of sensory evaluation [24]. Our PCA results indicated that salmon has a slow metamorphism rate in the early stage of storage at 25 °C, and the rate of decay in the later stage is accelerated (Figure 2).…”
Section: Discussionmentioning
confidence: 89%
“…Volatile compounds have been shown to change during storage, which can be used as good indicators of fish spoilage or shelf-life instead of sensory evaluation [24]. Our PCA results indicated that salmon has a slow metamorphism rate in the early stage of storage at 25 °C, and the rate of decay in the later stage is accelerated (Figure 2).…”
Section: Discussionmentioning
confidence: 89%
“…Especially ketones, mainly 3-hydroxy-2-butanone, TMA, and some alcohols [67,75]. Acetoin and 2-and 3-methyl-1butanol were proposed as potential fish quality markers: l [82]. Indeed, levels of acetoin increased earlier than TMA; therefore, it is more relevant to monitor the loss of freshness as an early indicator of spoilage [75] by monitoring such VOCs.…”
Section: Volatilome Analysis and Identification Of Specific Markersmentioning
confidence: 99%
“…VP or MAP result in a limited shelf life extension of seafood products compared to meat, due to CO 2 -resistant bacteria (namely P. phophoreum as previously stated) growth and metabolism [84,95]. As a result, studies focused on the identification of chemical indicators to characterize fish spoilage [82], when packed under anaerobic and/or modified atmosphere with CO 2 conditions. As already described in Figure 1, the initial headspace composition of packaged (AP, VP, and MAP) fish evolves by oxygen depletion and CO 2 production.…”
Section: Effect Of Atmosphere Compositionmentioning
confidence: 99%
“… 17 In contrast, SPME-GC/MS is a quantitative analytical method, 18 which has been used to study detailed volatile organic compounds (VOCs) in foods, such as prawns, 19 crabs, 20 and fish. 21,22 Parlapani et al found that some VOCs were associated with the metabolic activity of a particular microbial group, e.g. , ethyl esters were linked with Pseudomonas , while 2,3-methylbutanal and 3-hydroxy-2-butanone were associated with Carnobacterium and Lactobacillus .…”
Section: Introductionmentioning
confidence: 99%